Predominant but silent C1q deposits in mesangium on transplanted kidneys - long-term observational study - Kanai, Takahiro (BMC Nephrol, 2018)
BACKGROUND: C1q nephropathy (C1qN) was first described as glomerular disease characterized by predominant meangial C1q deposits in patients with proteinuria and no evidence of systemic lupus erythematosus. Several studies, however, revealed the clinical heterogeneity of C1qN, showing some cases with normal urinalysis. To confirm the existence of cases with predominant mesangial C1q deposits and negative or mild proteinuria and/or hematuria, we investigated renal graft biopsy specimens showing negative to mild proteinuria (less than or equal to 1+ by dip stick test) and/or hematuria. METHODS: Eligible participants were kidney transplant cases who corresponded to the criteria for C1qN and were followed more than 10 years. Their medical records were reviewed to determine the age at detection of predominant mesangial C1q deposits, gender, original renal disease and reason for renal graft biopsy, blood pressure, degree of proteinuria and hematuria, and serum creatinine levels. RESULTS: From 414 cases in adults and children, five pediatric patients (the male to female ratio, 1:1.5) were eligible. At the time when predominant mesangial C1q deposits were detected, 2 cases presented with mild proteinuria without hematuria, but the other 3 cases showed normal urinalysis. Light microscopy revealed minor glomerular abnormality in all the cases. Immunofluorescent study showed predominant mesangial C1q deposits with IgG, IgM and C3 in all cases. All selected specimens presented electron dense-depos in the mesangium. Ten years later from the detection, 2 cases continued to be normal urinalysis and 3 cases had mild proteinuria without hematuria. During this follow-up period, no cases presented with persistent proteinuria and/or hematuria greater than or equal to 2+ by dip stick test. And no cases developed systemic lupus erythematosus. Follow-up renal graft biopsies were performed once in 2 cases 8 years later from the detection. They showed minor glomerular abnormalities. C1q deposit disappeared in one case. In another case, immunofluorescent study was not examined. CONCLUSIONS: This long-term observational study on transplanted kidneys confirms the existence of cases with predominant but silent C1q deposits in the mesangium who have negative or mild proteinuria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12882-018-0874-9) contains supplementary material, which is available to authorized users.